Determining nursing students’ attitudes towards, readiness for, expectations from, and satisfaction with distance education and their sense of alienation from their university - Duygu Oztas; Fadime Toru; Senay Akgun; Funda Ozpulat (Journal of the Pakistan Medical Association)
Objective: To determine nursing students’ views on attitudes towards distance education during coronavirus disease 2019 pandemic.